2021
DOI: 10.15547/bjvm.2019-0134
|View full text |Cite
|
Sign up to set email alerts
|

The antimalaria drug artemisinin displays strong cytotoxic effect on leukaemia lymphocytes in combination with vitamin C and pro-vitamin K3

Abstract: This study investigated the anticancer effect of the anti-parasitic drug artemisinin in combination with two redox modulators: vitamin C and pro-vitamin K3 (C/K3) The experiments were conducted on leukaemia cells Jurkat. Cells were treated with either artemisinin or C/K3 alone and with all three compounds. Cell proliferation and viability were analysed using trypan blue stating and automated cell counting. The results showed that artemisinin (>10 mM) suppressed cell proliferation activity, but did not induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…106 Artemisinin, an antimalaria drug in combination with vitamin K3/AA treatment manifested an antiproliferative effect synergistically but not cell death at all concentration ratios in leukemia. 91 In the case of urothelial carcinoma, vitamin K3/AA treatment has significantly augmented the antineoplastic activity of gemcitabine both in vivo and in vitro by inducing apoptosis and suppressing cell proliferation. 72 It has been reported that vitamin K3/AA treatment in the bladder, prostate, and ovarian cancer arrested cell cycle at Go/Gl, S, G2/M-phases, and induced cell death by necrosis, apoptosis, and autoschizis.…”
Section: Vitamin K3 As a Chemosensitizermentioning
confidence: 99%
See 2 more Smart Citations
“…106 Artemisinin, an antimalaria drug in combination with vitamin K3/AA treatment manifested an antiproliferative effect synergistically but not cell death at all concentration ratios in leukemia. 91 In the case of urothelial carcinoma, vitamin K3/AA treatment has significantly augmented the antineoplastic activity of gemcitabine both in vivo and in vitro by inducing apoptosis and suppressing cell proliferation. 72 It has been reported that vitamin K3/AA treatment in the bladder, prostate, and ovarian cancer arrested cell cycle at Go/Gl, S, G2/M-phases, and induced cell death by necrosis, apoptosis, and autoschizis.…”
Section: Vitamin K3 As a Chemosensitizermentioning
confidence: 99%
“…A pile of literature suggested that parallel to promising anticancer activity of vitamin K3, it has also a strong potential to act as a chemosensitizer for multiple drug‐resistant neoplasms such as colon 26 62 and HTC116 63 cell lines of colon cancer; AN3CA 64,65 cell line of uterine cancer; DU145, 66–68 PC3, 69–71 and LNCaP 71 cell lines of prostate cancer; UC and UMUC‐14 72 cell lines of urothelial cancer; A431 73 cells line of epidermoid carcinoma; 253JB‐V,T24 72,74–77 and RT4 77,78 cell lines of bladder cancer; KB‐V1 79 cell line of cervix carcinoma; MDA‐MB 231 63 and MCF‐7 62,64,71,79–84 cell lines of breast cancer; A172 71 and U87MG 63 cell lines of glioblastoma; CG1 85 cell line of nasopharyngeal carcinoma; MOLT‐4, 86 K562, 87,88 HL‐60, 89 Jurkat, 62,63,90–92 , and CCRF‐CEM, K562 90,63 cell lines of leukemia; TLT 93 and HepG2 82 cell lines of HCC; HeLa 94 cell line of human cervical adenocarcinoma; MRC‐5 82 A549 94,95 and HCT116 96 cell lines of human colorectal carcinoma; RCC and ACHN 82,97 cell lines of renal carcinoma; KB, 64 HSC‐2, HSC‐3, and HGF 89 cell lines of human oral squamous cell carcinoma; MDAH 2774 98 and NCI/ADR‐RES 83 cell lines of ovarian carcinoma; and PANC1 71 cell line of human pancreatic cancer as given in Table 3.…”
Section: Chemosensitizing Mechanism Of Vitamin Kmentioning
confidence: 99%
See 1 more Smart Citation